Inflammatory Complications Related to Tattooing: A Histopathological Approach Based on Pattern Analysis. (January 2015) - Thum, Chee K.; Biswas, Asok
Abstract : Abstract: Although tattooing is an ancient practice, its increasing popularity and social acceptance, variability of tattoo ink composition, sporadic reports of novel tattoo reactions and advances in the field of tattoo removal techniques make it a topic of immense interest among dermatologists and pathologists alike. Since effective legislation governing the tattoo industry is largely lacking in most regions of the world, it is important to recognize the range of tattoo-related complications from a dermatopathological perspective. Using a pattern-based approach, this review details the broad spectrum of inflammatory reactions, which may be encountered in adverse reactions associated with tattooing. Awareness of the range of inflammatory tattoo reactions is crucial as some of these patterns of inflammation can be associated with systemic disorders and others may serve as important clues for an underlying infective condition.